Impacto de um programa educativo e preventivo na mucosite oral, no acúmulo de biofilme e na condição gengival de pacientes oncológicos pediátricos - Sampaio, Maria Eduarda Alves (2019)
Poor oral hygiene is reported as a factor associated with the permanence of oral mucositis (OM) in cancer patients. Thus oral care is essential in oncological patient care. The aim of this study was to evaluate the impact of a educational and preventive program in oral health conditions and on the incidence/severity of OM in pediatric oncology patients, as well as to evaluate the perception of patients and their parents/caregivers in relation to the implemented program. A longitudinal intervention study with quantitative-qualitative approach was carried out. The study address was supported by all oncological patients attending the pediatric ward of the Hospital Napoleão Laureano (João Pessoa/PB) from April to 2018 and their parents/caregivers. The sample consisted of 27 children and adolescents, assessed before and after the institution of the program, through the Modified Oral Assessment Guide (OAG), Visible Plaque Index (VPI) and Modified Gengival Index (MGI) for ten weeks. Semi-structured interviews containing open-ended questions were applied to patients and caregivers, 15 and 30 days after the start of the program. It was used audiovisual resources, storytelling and play instruments for oral health education of patients and parents/caregivers. The quantitative data were evaluated by descriptive statistics and tested for their normality by the Shapiro-Wilk test, then the inferential analysis was performed with the Chi-square and Wilcoxon tests (α = 0.05). The information obtained through the interviews was analyzed using the Collective Subject Discourse (DSC) method. Prevalence of male patients (51.9%, n = 14), mean age of 9.21 (± 4.49) years, brown (66.7%, n = 18) and residents of inner cities (n = 21; 77.8%), being a more frequent pathology, Acute Lymphoid Leukemia (n = 6; 22%). The most widely performed therapeutic modality was exclusive chemotherapy (n = 17; 63%) and the most widely used chemotherapeutic class was natural products (n = 188; 66.9%). The MGI and VPI were higher before the institution of the oral health program with averages of 0.88 (± 0.58) and 54.11% (± 19.32%), respectively. At the end of the evaluated period there was a reduction in the averages on that indexes (MGI = 0.33; VPI = 19.83%). The occurrence of OM and MOG was more frequent in the second week of follow-up (n = 12, 66.7%, n = 6, 33.3%, respectively), whereas an inferential analysis revealed that there was a statistically significant difference (p<0.05) between the occurrence of OM and SOM (severe oral mucositis) in the studied period, with a higher incidence of SOM. The VPI and MGI indexes presented statistically significant difference between baseline and most of the evaluated x weeks. There was an association between OM and IGM in the 3rd week, and in the 5th week there was an association between SOM and the two indexes (p<0.05). Regarding patients and caregivers' perception of the program, there were improvements in habits and conditions of oral hygiene and increased vigilance regarding the appearance of oral alterations. It was concluded that the institution of an oral health program had a positive impact, contributing to the reduction of oral mucositis severity and helping to improve oral hygiene, as reported by patients and caregivers.